Similarities and differences in morphology, CD31 and CD68 expression of male vs. female sinoatrial node and its surrounding atrial muscle in ageing and obesity - Weixuan Chen; Jingmo Qu; Daniel Rams; Maciej Zajac; Raghad Albalawi; Abimbola Aminu; Malgorzata Mazur; Mateusz K. Holda; Jerzy Walocha; Krzysztof Gil; Marcin Kuniewicz; Halina Dobrzynski; et al. (Elsevier, 2024)
Research purpose: The sinoatrial node (SN) is the main pacemaker site, and it is located in the junctional area of the superior vena cava within the right atrium (RA). The precise micro-anatomy of the SN in males and females in ageing and obesity remains unclear. Basic procedures: Human SN/RA specimens were dissected from 25 post-mortem hearts (preserved in 4 % formaldehyde solution), under Polish local ethical rules. The SN/RA tissue blocks were embedded in paraffin. Masson's Trichrome staining and immunohistochemistry for CD31 (a marker of endothelial cells) and CD68 (a marker of macrophages) were performed. Images at different magnifications were taken and analysed. 12-lead ECGs from 24 patients under Polish local ethical rules were obtained. Heart rate and P wave morphologies from lead II, lead III and lead aVF were analysed. Statistical analysis was performed with the unpaired t-test. Principal results: Heart weight to body weight ratio was significantly higher in aged obese males vs. their female counterparts. In the RA samples, there was an increase in connective tissue and decreased myocyte content from aged obese females compared to aged obese males. Aged non-obese males had significantly increased cellular hypertrophy than the aged non-obese females. Both the aged obese and aged non-obese females showed more CD3 but less CD68 expressing cells than males. In the SN samples, CD31 and CD68 expressing cells were higher in both aged non-obese and aged obese males than their female counterparts. Major conclusions: Ageing and/or obesity are more likely to impact these cardiac tissues through increased inflammation, increased immune response and hypertrophy.